Artificial insemination services under different institutional framework in Bangladesh (Bangladesh Journal of Animal Science, 2015)
The objective of the study was to compare the provision of the existing artificial insemination service delivery system (AI-SDS) among public, private and autonomous institutions to the small-scale dairy farmers in Bangladesh. A cross-sectional survey was conducted by using a pre-tested and pre-designed questionnaire and face-to-face interview technique. A stratified-purposive sampling technique was applied to select 165 small-scale dairy farmers from four study areas. Descriptive statistics were performed to know the frequency of the provision of AI services. Public services were available in all study areas whereas autonomous services were only delivered in Mymensingh district. The private service was increasing faster than the public and autonomous service. The public service had higher incentives and network coverage compared to private and autonomous services. The results also showed that 50% of the respondent perceived the AI service as public goods and showed no willingness to pay (e.g., free of charge for public service). The demand for the services has been increasing but the existing organizations were not able to provide the services especially to the remote areas. From this study, it is recommended that farmers needs should be translated in a way that they get access to their required services in a satisfactory manner.DOI: http://dx.doi.org/10.3329/bjas.v43i3.21643 Bang. J. Anim. Sci. 2014. 43 (3): 166-174